CONGENITAL TOXOPLASMOSIS: A NARRATIVE REVIEW (CIPEEX, 2024)
The aim of this study was to promote a literature review on toxoplasmosis and its consequences in prime infection during pregnancy. A bibliographic review of the narrative type was promoted with research of scientific articles in the databases SciELO, PubMed and Google Scholar, using the keywords: toxoplasmosis, Toxoplasma gondii, congenital toxoplasmosis and pregnancy. Publications in English were included in the study and Portuguese made available in full within five years. From this literature review it was verified that toxoplasmosis is a protozoosis caused by the parasite Toxoplasma gondii. Its transmission occurs after the ingestion of sporulated oocysts of T. gondii, which are released into the environment after performing sexual cycle in felines, being eliminated in the feces of contaminated cats. Thus, they may be present in contaminated water due to lack of basic sanitation, consumption of raw or undercooked meat and contact with infected sand, among others. Vertical transmission occurs by transplacental route and is called congenital toxoplasmosis. Each region has a demographic characteristic that can influence the increase in infection. Pregnant women with toxoplasmosis in the acute phase may present with symptoms suggestive of primary infection, especially fever, headache, lymph node enlargement, asthenia, myalgia, and sore throat. Congenital toxoplasmosis can cause a few consequences for the fetus, such as premature birth, intellectual disability, severe developmental delays, intrauterine growth restriction, jaundice, hepatosplenomegaly, intracranial calcifications, hydrocephalus or retinochoroiditis. Because it has a major impact on human health, toxoplasmosis requires proper screening, diagnosis, and treatment to prevent or minimize its potential damage. Studies have reported on the prevalence of congenital infection by T. gondii to be between 0.6-1.3/1000 live births in Brazil. It was suggested that the chance of transplacental transmission, that is, from mother to fetus is variable between 18.5 and 23%. The risk of fetal infection in the first trimester is less than 15%, but in general, the disease is severe in the newborn. The risk of infection increases between 20 and 50% in the second trimester and between 55 and 80% in the third trimester of pregnancy, but the newborn is asymptomatic or has less severe disease. Primary Health Care (PHC) is considered the gateway to health services and has great relevance in the information transmitted for the monitoring of cases in multidisciplinary teams, being determinant for the change of behaviors and for the adoption of healthy lifestyle habits. It was concluded that toxoplasmosis is an important public health problem, especially when it causes harm to the fetus through vertical transmission; should be studied and oriented to the population and especially pregnant women, because it is a common disease and prevention and symptoms often unknown.